KUALITAS PELAYANAN PADA PELANGGAN PASANG BARU PT PLN (PERSERO) AREA KARAWANG - Amanda Morlian (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study to determine : (1) Quality of service to new tide customers PT PLN Persero Area Karawang, (2) Barriers to the quality of service to new tide customers PT PLN Persero Area Karawang, (3) Efforts made by PT PLN Persero Area Karawang in improving service quality. In expressing the quality f service t new high-end customers PT PLN Persero Area Karawang, using the Zeithmal, Parasuraman and Berry theory (in Hardiansyah 2011:46) which presents an element of service quality assessment consisting of : (1) Tangible (2) Reliability (3) Responsive (4) Assurance (5) Empaty. This type of research is quantitative. Data collection techniques are carried out through literature study, observation and questionnaire. The number of study population was 20 people. The results of the study show that the indicators of service quality on customer satisfaction at PT PLN Persero Area Karawang are considered good which means customers are satisfied with the service or performance of service providers and the quality influences customer satisfaction.